The Difference in Clinical and Prognostic Features Between De Novo and Recurrent Her2-Positive Metastatic Breast Cancer Patients: Her2-positive metastatic breast cancer patients - Acikgoz, Yusuf; Ergun, Yakup; Ucar, Gokhan; Dirikoc, Merve; Uncu, Dogan (Acta Medica, 2019)
Abstract BACKGROUND: There are different data in the literature about the consequences of the development of metastasis as de novo or recurrent. In this study, we retrospectively investigated the clinicopathologic and prognostic characteristics of HER-2 positive de novo and recurrent metastatic breast cancer (MBC) patients. PATIENTS AND METHODS: The data of patients admitted to our clinic between 1996-2017 were analyzed retrospectively. The baseline features, treatments and survival data were recorded. Recurrent metastatic patients were further categorized as disease free interval (DFI) <24 months and DFI >24 months. The features of two groups were analyzed by pearson chi-square test. Survival were calculated by using the Kaplan-Meier method with the Long-rank test. p <0.05 was considered statistically significant. RESULTS: A total of 44 patients were included to study in which 20 patients in de novo HER-2 positive MBC group and 24 patients in recurrent HER-2 MBC group. There was no difference in baseline features between groups. The median OS in de novo and recurrent MBC group was 60.3 months and 43.9 months respectively (HR: 0.87, 95% CI 0.37-2.05, p=0.76). OS was not different between de novo MBC group and patients with DFI <24 months and with DFI > 24 months (p=0.135). CONCLUSION: Our study showed that baseline features of patients with de novo HER-2 positive MBC and recurrent HER-2 positive MBC did not differ from each other. The presence of metastasis at the time of diagnosis or during follow-up did not change response to treatments.